Konstruksi Toleransi melalui Simbol Kalpataru - Fatih, Moh. Khoirul (Proceedings of Annual Conference for Muslim Scholars, 2024)
This research aims to uncover the construction of tolerance through the Kalpataru symbol in Sunan Bonang's artwork. Through a semiotic approach, this study will analyze the meanings contained in the Kalpataru symbol in various artworks associated with Sunan Bonang. The analysis will cover iconic, indexical, and symbolic aspects of the Kalpataru symbol to reveal how this symbol functions as a representation of the values of tolerance, diversity, and unity. This research is expected to contribute to a deeper understanding of the role of art in building an inclusive and tolerant society, as well as the relevance of the Kalpataru symbol in the contemporary Indonesian context.